2010
DOI: 10.1590/s1413-294x2010000300012
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco do tecnoestresse em trabalhadores que utilizam tecnologias de informação e comunicação

Abstract: O estudo objetivou identificar fatores de risco sociodemográficos, laborais e psicossociais em 668 trabalhadores de organizações de Porto Alegre (RS) e região metropolitana. Para a coleta de dados foi utilizada a Escala de Tecnoestresse (RED/TIC) e um questionário para levantamento das demais variáveis. O resultado obtido com relação à dimensão de "Descrença" estabeleceu um perfil de risco constituído por mulheres, com filhos e escolaridade em nível de ensino médio. A dimensão de "Fadiga" constituiu-se por mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
(10 reference statements)
0
5
0
5
Order By: Relevance
“…The best approach is to try and pro-actively diminish the psychosocial risks in the first place. To this end ILO provides detailed and up-to-date instructions (ILO, 1998;2012). In order to be reduced, the psychosocial risks must first be identified and assessed.…”
Section: Proposed Methods Of Assessment and Mitigation -Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The best approach is to try and pro-actively diminish the psychosocial risks in the first place. To this end ILO provides detailed and up-to-date instructions (ILO, 1998;2012). In order to be reduced, the psychosocial risks must first be identified and assessed.…”
Section: Proposed Methods Of Assessment and Mitigation -Future Workmentioning
confidence: 99%
“…According to recent data breach studies, insiders may directly or indirectly be behind a significant percentage of breaches, whether intentional or not (Verizon, 2009;2010;. The reported insider threat percentages varied from 17% to 48% of all data breach cases that were studied in the three-year period from 2009 to 2011.…”
Section: Effects On Information Securitymentioning
confidence: 99%
“…Estas situações, que à primeira vista parecem evidências de um "novo normal" advindas do ensino remoto, são clássicas nos estudos do trabalho, à medida que uma nova técnica ou ferramenta é inserida nos processos de trabalho (LEPLAT, CUNY, 1983) e, de modo geral, quando envolvem tecnologias digitais, podem levar ao fenômeno denominado tecnoestresse (CARLOTTO, 2010). Este seria um estado psicológico negativo de exaustão emocional relacionado ao uso (ou ameaça de uso) de tecnologias no ambiente de trabalho, caracterizado pela inabilidade de lidar de forma saudável com as tecnologias, que leva a situações de ansiedade nas quais o trabalhador vai perdendo gradativamente o controle emocional em relação às exigências do seu trabalho.…”
Section: Crise Pandêmica E Ubiquidade No Trabalho E Na Educaçãounclassified
“…Individuals also tend to experience lower levels of job satisfaction and they are more likely to negatively evaluate their work (Tarafdar et al, 2011;Pocinho & Garcia 2008). Several studies have indicated gender differences with respect to technostress, with males experiencing more technostress than females (Carlotto, 2010;Shu et al, 2011;Tarafdar et al, 2011). One possible reason for this is that males may be more inclined to voluntarily use ICT in situations were it is not entirely necessary, so they experience a greater number of technostresscreating conditions than females (Carlotto, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, women in certain contexts have also been reported to be at risk of technostress. A survey aiming to identify factors associated with technostress among this population in Brazil by Carlotto (2010) identified that woman with children and high school degrees, who were exposed to ICT, including email and mobile…”
Section: Introductionmentioning
confidence: 99%